A CLINICAL STUDY TO EVALUATE THE EFFICACY OF VAMANA KARMA IN THE MANAGEMENT OF DYSLIPIDEMIA - Singh, Shipra; Kumar Srivastava, Alok (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the present study is to evaluate the efficacy of Vamana karma in the management of dyslipidemia. Methods: Patients were selected from the OPD and IPD at the Department of Panchakarma, Hospital of Rishikul Campus, Uttarakhand Ayurved University, Haridwar. Patients in Group A will be administered with two sittings of Vamana procedure. In Group B, 20 patients will be treated with atorvastatin for 60 days in dose of 10 mg once daily after meals with water. Results: The overall assessment of the therapy was decided on the basis of improvement in biochemical parameter (serum lipid profile) by applying statistics. Vamana karma had statistically highly significant result in all the objective parameters except high-density lipoprotein [HDL]. Conclusion: Thus, it can be concluded that dyslipidemia is a form of Kaphavikara specifically may be Medodushti in the form of Abaddha meda. Vamana karma is highly effective in correcting serum lipid profile except HDL and very low-density lipoprotein but have better effect than the standard drug in both of them. Vamana karma can be used for the effective and safe management of dyslipidemia.